Effects of the 2014 Affordable Care Act Medicaid Expansions on Health Care Access and Health Status of Poor Adults Aged 60–64 Years: Evidence From the First 6 Years. (23rd December 2021) - Bin Abdul Baten, Redwan; Wehby, George L
Abstract: Background and Objectives: Little is known on the effects of the Affordable Care Act (ACA) Medicaid expansions on health care access and health status of adults closest to 65. This study examines the effects of ACA Medicaid expansion on access and health status of poor adults aged 60–64 years. Research Design and Methods: The study employs a difference-in-differences design comparing states that expanded Medicaid in 2014 under the ACA and nonexpansion states over 6 years postexpansion. The data are from the 2011–2019 Behavioral Risk Factor Surveillance System for individuals aged 60–64 years below the Federal Poverty Level. Results: Having any health care coverage rate increased by 8.5 percentage points ( p < .01), while the rate of forgoing a needed doctor's visit due to cost declined by 6.6 percentage points ( p < .01). Similarly, rates of having a personal doctor/provider and completing a routine checkup increased by 9.1 ( p < .01) and 4.8 ( p < .1) percentage points, respectively. Moreover, days not in good physical health in the past 30 declined by 1.5 days ( p < .05), with suggestive evidence for decline in days not in good mental health and improvement in self-rated health. Discussion and Implications: The ACA Medicaid expansions have improved health care access and health status of poor adults aged 60–64 years. Expanding Medicaid in the states that have not yet done so would reduce barriers to care and address unmet health needs for this population. Bridging coverage for individuals aged 60–64 years by lowering Medicare eligibility age could have long-term effects on well-being and health services utilization.